2020
DOI: 10.1177/0266666920976181
|View full text |Cite
|
Sign up to set email alerts
|

Health Information behaviour during COVID-19 outbreak among Egyptian library and information science undergraduate students

Abstract: Health information shared on the Internet has the potential to improve people’s quality of life. However, the level of health information literacy and informational skills determines the individuals’ ability to obtain credible health information useful for them. This study investigates the Egyptian LIS undergraduates’ health information behaviour during the COVID-19 pandemic. The study has adopted a quantitative approach using a questionnaire to explore library and information science undergraduates’ health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 36 publications
4
39
0
4
Order By: Relevance
“…Health information is more reliable as they are designed by experts (Chen et al, 2020) and e-government (Park and Lee, 2018). Information credibility and primary sources of official websites, social media, families and friends capture an important role in health information behavior during COVID-19 (Shehata, 2020). Park (2020) supported the positive impact of source credibility on information usefulness, which results in information adoption toward social media.…”
Section: Source Credibility (Cre)mentioning
confidence: 98%
See 1 more Smart Citation
“…Health information is more reliable as they are designed by experts (Chen et al, 2020) and e-government (Park and Lee, 2018). Information credibility and primary sources of official websites, social media, families and friends capture an important role in health information behavior during COVID-19 (Shehata, 2020). Park (2020) supported the positive impact of source credibility on information usefulness, which results in information adoption toward social media.…”
Section: Source Credibility (Cre)mentioning
confidence: 98%
“…Furthermore, if users gain information, they will express sentiments and adopt the diffusion of healthcare knowledge (Oh and Lee, 2019). Other scholars supported that information usefulness boosts information adoption toward social media (Park, 2020) and health information skills under COVID-19 (Shehata, 2020). Al-Omairi et al (2020) found that relevant, timely information acts a crucial role in fostering credibility toward e-government services.…”
Section: Conceptual Model and Hypotheses 231 Information Relevance (Rel)mentioning
confidence: 99%
“…In line with our study, a study by Schäfer et al 37 showed that German students primarily searched for information on COVID‐19 online. A study in Egypt also found that students preferred online websites to learn about the COVID‐19 38 …”
Section: Discussionmentioning
confidence: 99%
“…We included also social networking sites (SNS) in our research as these sites have become a notable source of information for some individuals. The COVID-19 pandemic motivated people to increase their search for health information on the Internet, which, however, oftentimes caused more confusion and anxiety instead of helping (Mohammadi et al 2020;Shetata 2020).…”
Section: Conceptual Framework and Research Questionsmentioning
confidence: 99%